2021
DOI: 10.3389/fchem.2021.662659
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sampling and Storage Conditions on the Metabolite Profile of the Marine Sponge Geodia barretti

Abstract: Geodia barretti is a deep-sea marine sponge common in the north Atlantic and waters outside of Norway and Sweden. The sampling and subsequent treatment as well as storage of sponges for metabolomics analyses can be performed in different ways, the most commonly used being freezing (directly upon collection or later) or by storage in solvent, commonly ethanol, followed by freeze-drying. In this study we therefore investigated different sampling protocols and their effects on the detected metabolite profiles in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…This would constitute a valuable reference pattern to assess data taken from similar models in which treatments such as graft technologies or other therapeutics are utilized, and would afford a more direct means of objective comparisons between dissimilar therapeutics. Sample collection was performed immediately following bulk extraction of the defect site and preserved at −80°C within 1 h postmortem to prevent degradation of analytes ( 36 ). To better compare the small molecule intensity data between different time points, in which increasing mineral content made metabolite extraction more difficult, the values associated with any given small molecule were normalized to present as a percentage of the overall metabolite distribution profile in addition to an initial normalization by sample weight.…”
Section: Discussionmentioning
confidence: 99%
“…This would constitute a valuable reference pattern to assess data taken from similar models in which treatments such as graft technologies or other therapeutics are utilized, and would afford a more direct means of objective comparisons between dissimilar therapeutics. Sample collection was performed immediately following bulk extraction of the defect site and preserved at −80°C within 1 h postmortem to prevent degradation of analytes ( 36 ). To better compare the small molecule intensity data between different time points, in which increasing mineral content made metabolite extraction more difficult, the values associated with any given small molecule were normalized to present as a percentage of the overall metabolite distribution profile in addition to an initial normalization by sample weight.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the availability of the spectral library of a compound is very important in accelerating such identification. Several studies on metabolomics in sponges and their associated microbes reported that the use of LC-MS and GC-MS resulted in complex chemical profiles, thus requiring a reliable spectral library to assist the identification process; several studies used molecular networking methods combined with a cluster analysis in the identification of compounds (Alkhalifah, 2021;Erngren et al, 2021;Fagundes et al, 2021;Ho et al, 2021;Yuliana et al, 2011). Therefore, it is highly recommended to apply metabolomics on sponges and their associated microbes whose active compounds are not known using chromatographic techniques combined with MS by conditioning the type of compounds to be separated and conducting chemical profiles to facilitate a multivariate data analysis.…”
Section: Analytical Methods For Metabolomicsmentioning
confidence: 99%
“…Thus, bioactivity tests will be easier and simpler when the number of extract samples or fractions is quite large. The application of metabolomics to sponges and their associated microbes using the OPLS-DA chemometric technique has been done in many studies to be able to predict active or inactive samples (Ali et al, 2013;Bayona et al, 2018;Erngren et al, 2021;Tawfike et al, 2019a).…”
Section: Chemometric Methods For Metabolomicsmentioning
confidence: 99%
“…2003 ). This microbiota partly accounts for its richness in natural products ( Erngren et al . 2021 ; Steffen et al .…”
Section: Introductionmentioning
confidence: 99%